DETERMINAN PENYERAPAN ANGGARAN PADA SATUAN KERJA PERANGKAT DAERAH DI KOTA JAMBI - Ratumas Atiah, Nazma Ululbi; Zulfanetti; Mustika, Candra (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study aims to examine the factors that influence budget absorption, namely budget planning, budget implementation, human resources, and procurement of goods and services. The study population included 28 Regional Apparatus Organizations (OPD) in Jambi City, with a total of 84 respondents selected using purposive sampling techniques. Data analysis was conducted using panel data regression methods with the help of the Eviews program version 12. The results showed that all independent variables (budget planning, budget implementation, human resources, and procurement of goods and services) had a positive effect on budget absorption. In addition, these variables were able to explain 99.13% of budget absorption, while the remaining 0.87% was influenced by other factors outside the research model.